HSSB1 (NABP2/OBFC2B) is regulated by oxidative stress - O'BYRNE, KEN (My University, 2016)
The maintenance of genome stability is an essential cellular process to prevent the development of diseases including cancer. hSSB1 (NABP2/ OBFC2A) is a critical component of the DNA damage response where it participates in the repair of double-strand DNA breaks and in base excision repair of oxidized guanine residues (8-oxoguanine) by aiding the localization of the human 8-oxoguanine glycosylase (hOGG1) to damaged DNA. Here we demonstrate that following oxidative stress, hSSB1 is stabilized as an oligomer which is required for hSSB1 to function in the removal of 8-oxoguanine. Monomeric hSSB1 shows a decreased affinity for oxidized DNA resulting in a cellular 8-oxoguanine-repair defect and in the absence of ATM signaling initiation. While hSSB1 oligomerization is important for the removal of 8-oxoguanine from the genome, it is not required for the repair of double-strand DNA-breaks by homologous recombination. These findings demonstrate a novel hSSB1 regulatory mechanism for the repair of damaged DNA.
Keywords: genome stability; genome stability